Ad hoc on-demand distance vector (AODV) routing protocol invehicular ad hoc network (VANET): An analysis study - Idris, Ariff; Ismail, Mahamod; Nordin, Rosdiadee; Baharon, Mohd Rizuan; Azzam, Nurfatihah; Jaya Kumar, Yogan; Raja Ikram, Raja Rina; Hasan Basari, Abd Samad; Abdul Hamid, Mohd Hakim; Salahuddin, Lizawati (Science and Engineering Research Support Society, 2019)
One of variation Mobile Ad-hoc Network(MANET) is a Vehicular Ad Hoc Network (VANET). Vanet also part of Intelligent Transportation Systems (ITS) that uses cars as nodes of a network of a mobile network . The communication types in VANET are categorized into three types which are vehicle-to-vehicle communication (V2V), vehicle-to-roadside communication (V2R) and vehicle-to-infrastructure communication (V2I) [2]. The routing protocol investigated in this research is topology-based ad hoc routing protocol that is Ad hoc On- Demand Distance Vector (AODV). The routing analysis of this protocol is evaluated based on throughput and packet drop. This research investigates the latest trend of routing protocol used in VANET, evaluate the routing protocol in VANET using TWO (2) performance parameters and to implement the routing protocol in VANET in network simulator. This research was conducted using Network Simulator (NS-3) simulation